THE ROLE OF PREGNANCY-SPECIFIC GLYCOPROTEIN IN REGULATION OF MOLECULAR GENETIC DIFFERENTIATION MECHANISMS OF IMMUNE MEMORY T CELLS - M. B. Rayev (SPb RAACI, 2019)
The role of pregnancy-specific β1-glycoprotein (PSG) in the regulation of molecular genetic factors determining the functional activity of naїve T cells and T cells of immune memory in vitro was studied. Human PSG was isolated with a proprietary immuno-purification method using a biospecific sorbent followed by removing of immunoglobulin contamination with a HiTrapTM Protein G HP column. Physiological concentrations of PSG were used in the experiments. They corresponded to PSG levels in the peripheral blood of pregnant woman: 1, 10 and 100 μg/ml (I, II, III trimester, respectively). The objects of study were monocultures of naїve T cells (CD45RA+) and memory T cells (CD45R0+), obtained by immunomagnetic separation from the peripheral blood of women of reproductive age.It was established that at the level of naїve T cells (CD45RA+) PSG inhibited the expression of CD28 (1, 10, 100 μg/ml) and CD25 (100 μg/ml), without affecting the interleukin-2 (IL-2) production by these cells. At the same time, PSG in all concentrations studied suppressed the expression of CD25 at the immune memory T-cell (CD45R0+) surface but increased the IL-2 production. Expression of U2af1l4, Gfi1, hnRNPLL genes regulating the alternative splicing of the Ptprc gene encoding CD45 was also evaluated. It was found, that PSG reduced the expression of the Gfi1 (1, 10, 100 μg/ml), hnRNPLL (10, 100 μg/ml) genes, but increased the expression of the U2af1l4 gene (1, 10, 100 μg/ml) in the naїve T cells. It was shown that at the immune memory T-cells’ level the effects were similar, with PSG rendering them in all concentrations used. The revealed changes in the mRNA transcription of U2af1l4, Gfi1 and hnRNPLL genes in the studied T cell subsets may lead to the inhibition of CD45 “mature” isoform formation – CD45R0.Thus, PSG reduces the functional activity of naїve T cells and immune memory T cells associated with the expression of costimulation/activation molecules CD25 and CD28 and is involved in the regulation of Ptprc gene alternative splicing, which determines the ratio of CD45 molecule variants. Apparently, using these mechanisms, PSG regulates the functional activity of the memory T cell circulating pool, which is potentially capable of carrying out antigen-specific cytotoxic reactions against fetal antigens in vivo. In general, the data obtained broadens the notion of the PSG role in the regulation of molecular-genetic mechanisms of naїve T cells and immune memory T cells differentiation.